Boron nitride nanotube‐enhanced osteogenic differentiation of mesenchymal stem cells. Issue 2 (12th March 2015) - Li, Xia; Wang, Xiupeng; Jiang, Xiangfen; Yamaguchi, Maho; Ito, Atsuo; Bando, Yoshio; Golberg, Dmitri
Abstract: The interaction between boron nitride nanotubes (BNNTs) layer and mesenchymal stem cells (MSCs) is evaluated for the first time in this study. BNNTs layer supports the attachment and growth of MSCs and exhibits good biocompatibility with MSCs. BNNTs show high protein adsorption ability, promote the proliferation of MSCs and increase the secretion of total protein by MSCs. Especially, BNNTs enhance the alkaline phosphatase (ALP) activity as an early marker of osteoblasts, ALP/total protein and osteocalcin (OCN) as a late marker of osteogenic differentiation, which shows that BNNTs can enhance osteogenesis of MSCs. The release of trace boron and the stress on cells exerted by BNNTs with a fiber structure may account for the enhanced differentiation of MSCs into osteoblasts. Therefore BNNTs are potentially useful for bone regeneration in orthopedic applications. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 323–329, 2016.